Studi Komparasi Model Service Quality dan Model Library Quality dalam Pengukuran Kualitas Layanan Perpustakaan - Ramadhan, Ndaru (Perpustakaan Nasional, 2025)
There are various ways to measure service quality, including the ServQual Model and the LibQual Model. This study aims to determine the service quality measurement model that is more suitable for the Balai Layanan Perpustakaan DPAD DIY. This study uses a comparative descriptive approach by comparing two research objects, namely the ServQual Model and the LibQual Model. Based on the results of the analysis, it can be seen that there are differences between the ServQual Model and the LibQual Model. All dimensions in the ServQual Model have been covered by the LibQual Model. In addition, the Libqual Model also has dimensions of Library as Place, Personal Control, and Information Access. The difference in dimensions causes differences in measurement indicators in the ServQual Model and the LibQual Model. In addition, there are differences in the results of measuring service quality using the PANRB Regulation No. 14/2017 Model with the LibQual Model. This study is able to contribute as a consideration for the Balai Layanan Perpustakaan DPAD DIY in choosing service quality measurement tools, as an aid in policy formulation and service development, and advancing library science through the provision of study materials.